High-durability catalytic electrode composed of Pt nanoparticle-supported carbon nanowalls synthesized by radical-injection plasma-enhanced chemical vapor deposition. (11th September 2017) - Imai, Shun; Kondo, Hiroki; Cho, Hyungjun; Kano, Hiroyuki; Ishikawa, Kenji; Sekine, Makoto; Hiramatsu, Mineo; Ito, Masafumi; Hori, Masaru
Abstract: For polymer electrolyte fuel cell applications, carbon nanowalls (CNWs) were synthesized by radical-injection plasma-enhanced chemical vapor deposition, and a high density of Pt nanoparticles (>10 12 cm −2 ) was supported on the CNWs using a supercritical fluid deposition system. The high potential cycle tests were applied and the electrochemical surface area of the Pt nanoparticle-supported CNWs did not change significantly, even after 20 000 high potential cycles. According to transmission electron microscopy observations, the mean diameter of Pt changed slightly after the cycle tests, while the crystallinity of the CNWs evaluated using Raman spectroscopy showed almost no change.